KEARIFAN LOKAL DI SD NEGERI 2 KARANGLUHUR - Aditya Yoga Syahputra; Karima Faizatunni’mah; Lathifaturrahmah; Nurul Afifah; Nugroho Prasetya Adi (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to examine the implementation of local wisdom values in the learning process and to explore its impact on student character development. The research employed a descriptive qualitative approach, utilizing in-depth interviews and classroom observations for data collection. The findings revealed that local cultural values have been incorporated into various subjects such as Science and Social Studies (IPAS), Indonesian Language, and Civic Education (PP). These values include the introduction of regional traditions, the cultivation of tolerance, and the use of local food (carica) in procedural text lessons. Although local wisdom has been integrated conceptually, its practical application remains limited due to insufficient lesson planning and the dominant influence of religious values in the surrounding community. Nonetheless, the integration of local wisdom plays a significant role in enhancing students’ understanding of their cultural heritage and in supporting character education.